Vascular endothelial microparticles-incorporated microRNAs are altered in patients with diabetes mellitus. Issue 1 (December 2016) - Jansen, Felix; Wang, Han; Przybilla, David; Franklin, Bernardo; Dolf, Andreas; Pfeifer, Philipp; Schmitz, Theresa; Flender, Anna; Endl, Elmar; Nickenig, Georg; Werner, Nikos
Abstract Background Circulating microRNAs (miRs) are differentially regulated and selectively packaged into microparticles (MPs). We evaluated whether diabetes mellitus alters circulating vascular and endothelial MP-incorporated miRs expression levels. Methods and results Circulating MPs were isolated from 135 patients with or without diabetes mellitus type II and characterized using flow cytometer and electron microscope. Nine miRs involved in the regulation of vascular performance—miR-126, miR-222, miR-let7d, miR-21, miR-30, miR-92a, miR-139, miR-199a and miR-26a—were quantified in circulating MPs by reverse transcription polymerase chain reaction. Among those, miR-126 and miR-26a were significantly reduced in diabetic patients compared to non-diabetic patients. Patients with low miR-26a and miR-126 levels were at higher risk for a concomitant coronary artery disease. MP-sorting experiments showed that endothelial cells were the major cell sources of MPs containing miR-126 and miR-26a, respectively. Finally, in accordance with our clinical results, in vitro experiments revealed that hyperglycemia reduces the packaging of miR-126 and miR-26a into EMPs. Conclusion Diabetes mellitus significantly alters the expression of vascular endothelial miRs in circulating endothelial MPs with potential implications on vascular heath.